Penerapan Sistem Pembelajaran Interaktif Berbasis Augmented Reality Khusus Difabel - Putra, Ova Nurisma; Sumardi, Idi (STMIK IKMI Cirebon, 2021)
Education is a necessity that must be possessed by every human being, regardless of whether normal or disabled, especially for the disabled. This research aims to improve the quality of education for the disabled by providing confidence and the ability to receive lessons to be more interesting and interactive about what is conveyed by the teacher. The application of information technology in interactive learning systems is very helpful in the learning process for people with disabilities. The latest technology used in the delivery of information is the technology of Augmented Reality (AR). AR is a technology that combines three-dimensional (3D) virtual objects into a real three-dimensional environment at the same time. The 3-dimensional model is commonly used as a teaching aid to make students better understand the material provided. AR provides a more realistic interaction and is a progress of a promising technology method that can motivate users to engage in a more active learning system. Augmented Reality can be built using the help of Vuforia and Unity 3D software. In this study explains the basic concepts of making AR applications, with the Marker Based Tracking method. While the development model used is the waterfall model which consists of five phases, namely analysis, design, implementation, testing and maintenance. The results of this study are interactive learning media applications with Augmented Reality that will be used by the disabled, especially in the city of Bandung and in general in all schools in Indonesia, through their supervisors, and the results of this study serve as a comparison for other researchers in the selection of topics, studies, the method to be applied